2014
DOI: 10.1002/tesj.156
|View full text |Cite
|
Sign up to set email alerts
|

The Making of an International Educator: Transnationalism and Nonnativeness in English Teaching and Learning

Abstract: In the last decade, international teacher recruitment has accounted for an unprecedented number of nonnative‐English‐speaking teachers (NNESTs) from around the world hired to work in public schools in urban areas in the United States. However, the worldwide trend of international teacher recruitment, and its implications for issues of language, power, and identity involving NNESTs in the United States, continue to be an underrepresented area of study. In this article, the author looks at her own journey as a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…For the first two installments, I encouraged TCs to focus on recounting their past and recent language‐related experiences. Before installment 1, TCs read six sample autoethnographies (Canagarajah, ; Corah‐Hopkins, ; Donnelly, ; Manara, ; L. E. Park, ; Solano‐Campos, ) for the purpose of familiarizing themselves with the genre of autoethnography as a legitimate research methodology. Additionally, I devoted class time to the discussion of the intertwined nature of teacher learning and identity (Olsen, ), as well as the concepts of discourse and language ideologies in education (Pavlenko & Blackledge, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the first two installments, I encouraged TCs to focus on recounting their past and recent language‐related experiences. Before installment 1, TCs read six sample autoethnographies (Canagarajah, ; Corah‐Hopkins, ; Donnelly, ; Manara, ; L. E. Park, ; Solano‐Campos, ) for the purpose of familiarizing themselves with the genre of autoethnography as a legitimate research methodology. Additionally, I devoted class time to the discussion of the intertwined nature of teacher learning and identity (Olsen, ), as well as the concepts of discourse and language ideologies in education (Pavlenko & Blackledge, ).…”
Section: Methodsmentioning
confidence: 99%
“…Autoethnography is an established qualitative methodology in the social sciences (Denzin, ). It has recently gained traction as an emerging genre of research in language education (Canagarajah, ; Mirhosseini, ; Solano‐Campos, ). Autoethnography is based on narrative ontological and epistemological commitments.…”
Section: Critical Autoethnographic Narrative As a Teacher Learning Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the second strand include critical autoethnographies in which TESOL scholars (e.g., Canagarajah, ; Solano‐Campos, ) highlight how their transnational/translinguistic identities intersected with racial and sociopolitical discourses to shape their professional journeys as teachers and as scholars, but not as teacher educators. While these studies provide important insights about the developmental trajectory of some dimensions of TESOLers, they do not shed light on their work preparing teachers.…”
Section: Related Literaturementioning
confidence: 99%
“…Mirhosseini () argued that despite the growing interest of autoethnography in other fields of studies, its presence in the TESOL field has been marginal and scattered. Although this might be true, I think autoethnography has demonstrated a steady popularity as a method of choice in interrogating the nativespeakerism ideology embedded in TETs’ teacher identity construction when teaching in English‐dominant countries (Canagarajah, ; Jain, ; Lee, ; Liu, ; Manara, , Park, ; Solano‐Campos, ; Widiyanto, ) as well as in other non‐English‐dominant countries (Ng, ). These studies have demonstrated the significant, oftentimes unexpected ways in which autoethnography has created a dialogizing space to unravel the conflicting narrative voices surfaced by the nativespeakerism ideology.…”
Section: (Un)finalized Remarksmentioning
confidence: 99%